2018
DOI: 10.1021/acs.macromol.8b01656
|View full text |Cite
|
Sign up to set email alerts
|

Complex Hydrogels Based on Multiply Interpenetrated Polymer Networks: Enhancement of Mechanical Properties via Network Multiplicity and Monomer Concentration

Abstract: We present the preparation and study of the compressive mechanical and swelling properties of multiply interpenetrated, from double to quintuple (5-fold), polymeric hydrogels based on N,N-dimethylacrylamide (DMAAm) crosslinked with N,N′-methylenebis(acrylamide) (MBAAm), using five different monomer concentrations, from 1 to 5 M. Our results showed enhancement of the fracture stress, fracture energy density, and Young's modulus with network multiplicity and DMAAm monomer concentration. Fracture strain was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The design and use of cross-linking agents might be the key to the future of functional microgels. In the research of bulk gels, new technologies such as interpenetrating polymer network [ 97 , 98 ], nanocomposite gel [ 99 ], tetra-gel [ 100 ], and slide ring gel [ 101 ] have been applied to get the gels with a characteristic nanostructure.…”
Section: Remaining Problems On Functional Microgels and Strategiesmentioning
confidence: 99%
“…The design and use of cross-linking agents might be the key to the future of functional microgels. In the research of bulk gels, new technologies such as interpenetrating polymer network [ 97 , 98 ], nanocomposite gel [ 99 ], tetra-gel [ 100 ], and slide ring gel [ 101 ] have been applied to get the gels with a characteristic nanostructure.…”
Section: Remaining Problems On Functional Microgels and Strategiesmentioning
confidence: 99%
“…However, these electrical charges in the polymers may be undesired for certain applications involving, for example, biomacromolecules, such as proteins, DNA, RNA, or polysaccharides, which are usually also charged and may interact electrostatically with the DN hydrogel. The charge problem has since been addressed by the replacement of the polyelectrolyte first network by nonionic polymer first networks and their interpenetration more than once, and, in particular, twice, three and four times, leading to triple (TN), quadruple (QN), and quintuple (5 × N) networks, respectively, to make up for the much lower equilibrium swelling of the nonionic first network compared to its polyelectrolytic counterpart used in the classical DN hydrogels. The approaches of TN, QN, and 5 × N hydrogels were successful, by providing totally nonionic multiple network hydrogels with enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, our group [29] reported the preparation and study of the compressive mechanical properties of quintuple (5×N) polymer hydrogels (and also their SN, DN, TN and QN precursors) of DMAAm cross-linked with MBAAm, and using five different monomer concentrations, from 1 to 5 M. We found that as network multiplicity and DMAAm monomer concentration increased, fracture stress and Young’s modulus also increased. This resulted in the quintuple network prepared at 5 M DMAAm concentrations being the best-performing multiple polymer hydrogel, displaying a compressive fracture stress and a compressive Young’s modulus of 51 and 2.1 MPa, respectively.…”
Section: Network Structures With Improved Mechanical Propertiesmentioning
confidence: 99%
“…In a very recent study [30], we used nanoindentation to characterize the hardness of some of the above-mentioned [29] multiple network hydrogels. Nanoindentation is a modern method for the characterization of the mechanical properties of even very fragile materials, with the requirement for only a small amount of sample.…”
Section: Network Structures With Improved Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation